Brexit on Stage: Two Verbatim Projects in Progress - Kębłowska-Ławniczak, Ewa (Porównania, 2021)
The article deals with two post-Referendum projects launched by British national organizations, the National Theatre and the Guardian with Headlong, whose task was to reflect more accurately on a broader range of current British experience. The projects were written in response to questions on whether national artistic institutions, the subsidized “complex culture,” have not been out of touch with the rest of the country, notably the post-Referendum crisis. Both projects set out to research the crisis with documentary and quasi-documentary methods, to involve in an exercise in “listening” and to focus on polarisation, voter fatigue and lack of trust. The article concentrates on the two projects as variants of political theatre and on the ways they use the verbatim method in their attempts to diagnose and understand the crisis arguing, further on, that the effects differ, leading either to populism or to empathetic understanding and reconciliation.